Kinematische Analyse von 3D-rekonstruierten Bewegungen der Lendenwirbelsäule und des Beckens beim Beagle in Schritt und Trab - Wachs, Katja (Tierärztliche Hochschule, 2015)
It is generally accepted that mammalian locomotion is characterized by a complex interaction between limb and back movements and that small intervertebral movements additively result in whole spine movements and pelvic displacements, (i. e. in the sagittal body plane during asymmetrical gaits). In comparison to the large amount of studies that investigated kinematics and kinetics of limb movements, as well as recordings of muscle activities of several limb muscles during locomotion, our knowledge of the axial system is surprisingly small, especially regarding pelvic and intervertebral movements. It was hence the aim of this study to quantify and analyze in vivo three-dimensional (3D) lumbar intervertebral and pelvic movements occurring during locomotion utilizing symmetrical gaits in dogs with a non-invasive method. For this, we used ‘Scientific Rotoscoping’, a non-invasive method in the X-ray reconstruction of moving morphology (XROMM). By using a digital high-speed, high-resolution system, we recorded biplanar x-ray videos of the movements of the lumbar spine and pelvis of three Beagles while walking and trotting on a horizontal treadmill. By using CT-scans of each dog, 3D bones were reconstructed and aligned by using ‘virtual joints’ with integrated measurement coordinate systems (ACS) to a digital marionette. Step by step alignment of the digital marionette to the movements of the bony structures seen in the x-ray videos allowed a detailed animation of the occurring joint movements and simultaneous measurement of 3D joint kinematics. Synchronous to the x-ray-video-recordings, two standard-light high-speed video cameras recorded the foot placements used by each dog during locomotion, allowing analysis of joint kinematics in relation to the footfall events. For the first time, we quantified 3D intervertebral movements of the lumbar spine and associated pelvic displacements of dogs using symmetrical gaits and provided novel, non-invasive, in vivo data for their motion patterns. In both gaits, maximal ...